Metformin Decreases the High Plasminogen Activator Inhibition Capacity, Plasma Insulin and Triglyceride Levels in Non-Diabetic Obese Subjects - Vague, Ph; Juhan-Vague, I; Alessi, M C; Badier, C; Valadier, J (Thrombosis and Haemostasis, 1987)
We have previously observed a positive correlation between Plasminogen Activator Inhibition capacity (PA Inhibition), Body Mass Index (BMI) and plasma insulin levels in a population of non diabetic subjects. The anti diabetic biguanide Metformin which decreases insulin resistance has been reported to increase the blood fibrinolytic activity. Therefore we have studied the effect of Metformin on PA Inhibition levels in obese subjects with normal glucose tolerance. Eighteen obese women (O) (BMI: 31.4 ± 1.13, m ± S.E.M.) were compared to age matched controls (C) (BMI: 20.2 ± 0.8) and randomized to a 15 days treatment by Metformin (M) (1.7 g/day) or placebo (P) in a double blind study while on a weight maintaining diet. O compared to C had higher levels (m ± S.E.M.) of PA Inhibition (9 ± 1.8 IU/ml, versus 2.88 ± 0.29 p <0.01), lower euglobulin fibrinolytic activity (EFA) (4.95 ±1.17 mm versus 9 ± 0.29 p <0.05), higher plasma insulin (24.1 ±2.1. uU/ml), versus 12 ± 1 p <0.01) and triglyceride (1.32 ± 0.16 mmol/1, versus 0.8 ± 0.08 p <0.05). After 15 days of treatment, in group M a significant decrease in PA Inhibition (5.51 ± 1.4, versus 9.48 ±2.1 p <0.05) in plasma insulin (18.5 ±0.1, versus 24.5 ± 3.5, p <0.05) and plasma triglyceride (1.08 ± 0.1, versus 1.47 ± 0.3 p <0.05) and an increase in EFA (6.50 ± 0.28, versus 5.25 ± 0.35 p <0.05) were observed. No significant variation was observed in group P.
Keywords: Fibrinolysis; Obesity; Metformin; Plasminogen activator inhibition